Ultrahigh‐performance liquid chromatography coupled to ion mobility quadrupole time‐of‐flight mass spectrometry profiling and unveiling the transformation of ginsenosides by the dual conditions of citric acid and high‐pressure steaming. (28th August 2022) - Li, Wei; Wu, Xinlong; Wu, Mengfan; Yin, Jiaxin; Ding, Hui; Wu, Tong; Bie, Songtao; Li, Fangyi; He, Yongzhi; Han, Lifeng; Yang, Wenzhi; Song, Xinbo; et al.
Abstract : Rationale: Many methods have been reported for the production of rare ginsenosides, including heat treatment, acid hydrolysis, alkaline hydrolysis, enzymatic hydrolysis, and microbial transformation. However, the conversion of original ginsenosides to rare ginsenosides under the dual conditions of citric acid and high‐pressure steam sterilization has rarely been reported. Methods: In this study, a method involving ultrahigh‐performance liquid chromatography coupled to ion mobility quadrupole time‐of‐flight mass spectrometry was developed for analysis of chemical transformation of protopanaxatriol (PPT)‐type ginsenosides Rg1 and Re, protopanaxadiol (PPD)‐type ginsenoside Rb1, and total ginsenosides in the dual conditions of citric acid and high‐pressure steam sterilization. An internal ginsenoside database containing 126 known ginsenosides and 18 ginsenoside reference compounds was established to identify the transformation products and explore possible transformation pathways and mechanisms. Results: A total of 54 ginsenosides have been preliminarily identified in the transformation products of PPD‐type ginsenosides Rg1 and Re, PPD‐type ginsenoside Rb1, and total ginsenosides, and the possible transformation pathways were as follows: Rg1, Re → 20( S )‐Rh12, 20( R )‐Rh12 ; Rg1, Re → 20( S )‐Rh1, 20( R )‐Rh1 → Rk3, Rh4, Rh5 ; Rb1 → gypenoside LXXV; Rb1 → 20( S )‐Rg3, 20( R )‐Rg3 → Rk1, Rg5 ; Re → 20( S )‐Rg2, 20( R )‐Rg2 → 20( S )‐Rf2, 20( R )‐Rf2, Rg4, F4 . Conclusions: The results elucidated the possible transformation pathways and mechanisms of ginsenosides in the dual conditions of citric acid and high‐pressure steam sterilization, which were helpful for revealing the mechanisms of ginsenosides and enhanced safety and quality control of pharmaceuticals and nutraceuticals. Meanwhile, a simple, efficient, and practical method was developed for the production of rare ginsenosides, which has the potential to produce diverse rare ginsenosides on an industrial scale.